2000
DOI: 10.1016/s1044-0305(00)00113-6
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of 3-nitrotyrosine in biological tissues and fluids: Generating valid results by eliminating artifactual formation

Abstract: Reactive nitrogen species such as peroxynitrite can nitrate specific amino acids, whether free or protein bound, and 3-nitrotyrosine is believed to be one marker of this reaction. To examine the significance of this pathway in biological systems we have developed an accurate, sensitive, and specific assay for 3-nitrotyrosine based on combined liquid chromatography tandem mass spectrometry. Our approach allowed simultaneous analysis of both tyrosine and 3-nitrotyrosine and employs isotopomer standards (i.e., [1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
116
0
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(124 citation statements)
references
References 19 publications
7
116
0
1
Order By: Relevance
“…Tg SOD1 WT and G93A mice express transgenic SOD1 at the same level, as measured by densitometric analysis (data not shown), allowing accurate proteome map comparisons. Technical problems exist in the detection of nitrated proteins because (i) the modification is rare in tissues and in biological fluids, even in pathological conditions (10); (ii) the modification is lost in strongly reducing conditions and possibly also under the action of not yet identified denitrase enzymes (17,18); and (iii) common chemical and immunological methods may detect false-positive nitrated proteins (35,36). Therefore, special care was needed in each experiment to avoid under-or overestimation, as described under "Materials and Methods."…”
Section: Fig 3 Nt Immunoreactivity In Ventral Horn Of Transverse Sementioning
confidence: 99%
“…Tg SOD1 WT and G93A mice express transgenic SOD1 at the same level, as measured by densitometric analysis (data not shown), allowing accurate proteome map comparisons. Technical problems exist in the detection of nitrated proteins because (i) the modification is rare in tissues and in biological fluids, even in pathological conditions (10); (ii) the modification is lost in strongly reducing conditions and possibly also under the action of not yet identified denitrase enzymes (17,18); and (iii) common chemical and immunological methods may detect false-positive nitrated proteins (35,36). Therefore, special care was needed in each experiment to avoid under-or overestimation, as described under "Materials and Methods."…”
Section: Fig 3 Nt Immunoreactivity In Ventral Horn Of Transverse Sementioning
confidence: 99%
“…Previous studies have demonstrated that the artifactual generation of halogenated and nitrated oxidation products is a major problem during the analysis of biological material (42)(43)(44)(45)(46)(47). Indeed, some studies have found that virtually all of the oxidation products detected in tissue were generated artifactually (42,46,47).…”
Section: Ascorbate and Thiols Potently Inhibit Uracil Chlorination Bymentioning
confidence: 99%
“…Indeed, some studies have found that virtually all of the oxidation products detected in tissue were generated artifactually (42,46,47). This is particularly a problem when acidic conditions are used for sample hydrolysis or derivatization.…”
Section: Ascorbate and Thiols Potently Inhibit Uracil Chlorination Bymentioning
confidence: 99%
“…Regardless of the mechanism of formation in vivo, protein 3-NT levels provide a useful measure of the severity of tissue exposure to reactive nitrogen species and a telling indicator of inflammatory disease severity and progression Brodsky et al, 2004;HalejcioDelophont et al, 2001;Skinner et al, 1997;Upmacis et al, 2007). Semiquantitative immunological methods (Ischiropoulos, 1998), as well as quantitative high-pressure liquid chromatography (HPLC)-based methods that utilize ultraviolet-visible (UV/VIS) absorption, electrochemistry, and mass spectrometry (MS) for detection (Frost et al, 2000;Maruyama et al, 1996;Schwedhelm et al, 1999;Shigenaga et al, 1997;Yi et al, 2000), have all been employed for the quantification of protein 3-NT residues; each method offers its own particular strengths and limitations. Importantly, these alternative 3-NT detection methods differ widely with regard to their relative sensitivity, specificity, throughput, and accessibility (because of differing requirements for expensive and/or specialized instrumentation).…”
Section: Introductionmentioning
confidence: 99%